Challenging Ultra Grain Refinement of Ferrite in Low-C Steel Only by Heat Treatment - Park, Myeong-heom; Shibata, Akinobu; Tsuji, Nobuhiro (Frontiers in Materials, 2020)
It is well-known that grain refinement is one of the most effective ways to improve strength of metals without addition of alloying elements. In order to obtain bulky metals having ultrafine grained (UFG) microstructures with average grain sizes smaller than 1 μm, severe plastic deformation (SPD) processes have made a great success. However, there are still big barriers to realize UFG metallic materials, especially UFG steels, in large scale industries, since SPD processes usually need special techniques and equipment, and large deformation forces are required for heavy plastic deformations. Cyclic heat treatments to repeat martensitic transformation and austenitization have been known as a simple way to fabricate fine-grained austenitic structures in steels. In the present study, we tried to make final ferrite microstructures ultrafine in a low-C steel by means of the cyclic heat treatment. Evolution of microstructures during the cyclic heat treatment was systematically investigated, putting stress on the change of grain sizes of austenite and ferrite. The austenite grain size decreased with increasing the number of heat treatment cycles, and the minimum average austenite grain size obtained was 11 μm. By having furnace-cooling from austenite states with various grain sizes, ferrite microstructures with different mean grain sizes were fabricated. We could successfully obtain a fine-grained ferrite structure with a mean grain size of 4.5 μm and nearly a random texture through the heat treatment without deformation. Microstructural features and mechanical properties of the obtained fine-grained ferritic structures were investigated by SEM / EBSD measurements and a tensile test at room temperature. The specimens with ferrite + pearlite microstructure with the smallest average ferrite grain size of 4.5 μm managed both high strength (yield strength of 375 MPa and tensile strength of 500 MPa) and large tensile ductility (uniform elongation of 20% and total elongation of 39%) in the simple 2Mn-0.1C steel.